Implementation of Benson Relaxation to Lower Blood Pressure in Elderly Hypertensive Patients in Joyotakan Village, Serengan District, Surakarta - Kurnia Ayu Rahmawati; Mulyaningsih (Jurnal Kesehatan Komunitas Indonesia, 2025)
Background: Hypertension is a common health condition among older adults and a major risk factor for cardiovascular complications. Non-pharmacological interventions, such as Benson relaxation, offer a safe and accessible approach to blood pressure management in the elderly. Objective: This study aimed to evaluate the effect of Benson relaxation therapy on blood pressure reduction among older adults with hypertension in Joyotakan Village, Serengan District, Surakarta City, Indonesia. Methods: A descriptive case study design was employed with two elderly respondents diagnosed with stage I hypertension. Benson relaxation was administered once daily for three consecutive days, with each session lasting 10–20 minutes. Blood pressure was measured before and after each intervention. Inclusion criteria were: diagnosed hypertension, age ≥35 years, ability to communicate verbally, and willingness to participate. Exclusion criteria included altered consciousness or concurrent use of antihypertensive medication during the study. Results: Both respondents showed consistent reductions in systolic and diastolic blood pressure across all three days. Respondent Mrs. S’s blood pressure decreased from 145/100 mmHg to 130/80 mmHg (a reduction of 15/20 mmHg), shifting from Stage I hypertension to prehypertension. Respondent Mr. S’s blood pressure decreased from 142/105 mmHg to 120/77 mmHg (a reduction of 22/28 mmHg), reaching the normal range. Daily reductions ranged from 5–15 mmHg in systolic and 5–15 mmHg in diastolic pressure. Conclusion: Benson relaxation therapy demonstrated a positive effect in lowering blood pressure among elderly individuals with hypertension, supporting its use as an effective non-pharmacological nursing intervention in community settings.